2013
DOI: 10.1111/nph.12160
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of metabolic function in the giant kelp, Macrocystis pyrifera, across depth and season

Abstract: To increase knowledge of transcript diversity for the giant kelp, Macrocystis pyrifera, and assess gene expression across naturally occurring depth gradients in light, temperature and nutrients, we sequenced four cDNA libraries created from blades collected at the sea surface and at 18 m depth during the winter and summer.Comparative genomics cluster analyses revealed novel gene families (clusters) in existing brown alga expressed sequence tag data compared with other related algal groups, a pattern also seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 63 publications
0
28
1
Order By: Relevance
“…Basal M. pyrifera tissues have higher respiratory rates because of reduced light and increased pigmentation (Colombo-Pallotta et al 2006) and it therefore may be an energetically efficient site for the translocation of NO 3 − for reduction processes. In fact, Konotchick et al (2013) reported higher upregulation of nitrate reductase (an enzyme required to reduce NO 3 − ) in tissues from deeper in the water column compared to blades near the water's surface.…”
Section: Discussionmentioning
confidence: 99%
“…Basal M. pyrifera tissues have higher respiratory rates because of reduced light and increased pigmentation (Colombo-Pallotta et al 2006) and it therefore may be an energetically efficient site for the translocation of NO 3 − for reduction processes. In fact, Konotchick et al (2013) reported higher upregulation of nitrate reductase (an enzyme required to reduce NO 3 − ) in tissues from deeper in the water column compared to blades near the water's surface.…”
Section: Discussionmentioning
confidence: 99%
“…Laminaria digitata also exhibits a XC-NPQ seasonal pattern involving an increase of the VAZ pool size in spring compared to winter (Gévaert et al 2002). The canopy-forming Macrocystis pyrifera provides a striking example (Colombo-Pallotta et al 2006;Konotchick et al 2013;Ocampo-Alvarez et al 2013). Due to its height (about 18-20 m), this alga occupies the entire water column, such that the blades close to the surface are exposed to an underwater light environment with higher irradiance and stronger fluctuations.…”
Section: Brown Algaementioning
confidence: 99%
“…In M. pyrifera, a large VAZ pool is found in blades growing at the surface and exposed to high and changing light conditions (Ocampo-Alvarez et al 2013). This is concomitant with a higher expression of two LI818 isoforms ("LHC7" and "LHC8") (Konotchick et al 2013), as the functional orthologs of the diatom Lhcx and the green algal LHCSR (Niyogi and Truong 2013 and see also Morosinotto and Bassi, Chap 14;…”
mentioning
confidence: 99%
“…Several proteins identified in the course of this study have previously been reported as induced or differentially expressed by a range of abiotic stressors in macroalgae including Ec. siliculosus (Ritter et al 2010), the kelp species Laminaria digitata (Cosse et al 2009), M. pyrifera (Konotchick et al 2013) and Fucus sp. (Pearson et al 2010).…”
Section: The Ectocarpus Response To Eurychasma Infectionmentioning
confidence: 99%